Porphyromonas gingivalis, Treponema denticola and toll‐like receptor 2 are associated with hypertensive disorders in placental tissue: a case–control study. (28th May 2013) - Chaparro, A.; Blanlot, C.; Ramírez, V.; Sanz, A.; Quintero, A.; Inostroza, C.; Bittner, M.; Navarro, M.; Illanes, S. E.
Abstract : Aim(s): To explore the associations between the presence of periodontal pathogens and the expression of toll‐like receptors (TLR‐2 and TLR‐4) in the placental tissue of patients with hypertensive disorders compared to the placentas of healthy normotensive patients. Material and Methods: A case–control study was performed. From a cohort composed of 126 pregnant women, 33 normotensive healthy pregnant women were randomly selected, and 25 cases of patients with hypertensive disorders of pregnancy, including gestational hypertension and pre‐eclampsia, were selected. Placental biopsy was obtained after aseptic placental collection at the time of delivery. All of the samples were processed and analysed for the detection of Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, Fusobacterium nucleatum, Treponema denticola and Tannerella forsythia using the polymerase chain reaction (PCR) technique. Determination of the expressions of TLR‐2 and TLR‐4 was performed in samples of total purified protein isolated from placental tissues and analysed by ELISA. The data were assessed using descriptive statistics. The associations among variables were estimated through multiple logistic regression models and the Mann–Whitney test to evaluate the differences between the two groups. Results: A significant increase was observed in the expression of TLR‐2 in the placentas of patients with hypertensive disorders ( p = 0.04). Additionally, the multiple logistic regression models demonstrated an association between the presence of T. denticola and P. gingivalis in placental tissues and hypertensive disorders (OR: 9.39, p = 0.001, CI 95% 2.39–36.88 and OR: 7.59, p = 0.019, CI 95% 1.39–41.51, respectively). Conclusions: In the present study, pregnant women with periodontal disease presented an association in the placental tissue between the presence of T. denticola and P. gingivalis and hypertensive disorders. Additionally, increased expression of TLR‐2 was observed. However, further studies are required to determine the specific roles of periodontal pathogens and TLRs in the placental tissue of patients with pregnancy‐related hypertensive disorders.